Foreign Direct Investment dalam Skema Joint Venture: Analisis Dampak Sosial-Ekologis di Kawasan Industri Morowali - Nafoura Maharani Arl; Sang Ayu Putu Rahayu (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Foreign Direct Investment (FDI) represents a key instrument in stimulating national economic growth, especially in resource-based industries. This study aims to analyze the social and ecological impacts of foreign direct investment under a joint venture scheme in the Indonesia Morowali Industrial Park (IMIP), Central Sulawesi. Utilizing a juridical-sociological approach and qualitative descriptive method, this article explores secondary data obtained from regulations, government publications, and civil society reports. The findings reveal that while the joint venture between PT Bintangdelapan Group and Tsingshan Holding Group significantly contributes to regional economic growth and the success of Indonesia’s nickel downstreaming policy, it simultaneously generates adverse externalities, including social inequality, marginalization of local communities, and environmental degradation due to poorly regulated industrial activities. This imbalance underscores a governance gap in managing FDI within strategic industrial zones. Hence, the study proposes an integrative policy reform that places social justice and environmental sustainability as central pillars of Indonesia's FDI framework.